Genetics - Taylor, Robert 1948-; Gale Group (San Diego, Calif. Lucent Books, Thomson/Gale, 2004)
Discusses the history and current state of scientific understanding of genetics, exploring the roles of genes, DNA, and RNA, as well as the medical, legal, and ethical dimensions of such issues as genetic engineering and DNA evidence.
The age of genetics -- Inheritance -- Genes and DNA -- Genetic engineering -- Genes and health -- Genes and the law -- Genetics and the definition of "Human".
Electronic reproduction.
Keywords: Genetics -- Juvenile literature; Electronic books